Romania – From the Economic-Financial Crisis to the Covid 19-Crisis. Bugetary-Fiscal Emphases. Relevant Macroeconomic Indicators - Ramona Ciobanu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The COVID-19 pandemic has a strong impact on each individual, but also on society as a whole, on all fields of human activity, including economic activity and performance. This challenge came less than 10 years after the end of the economic-financial crisis and puts the economies of states to a new test of resilience, while verifying the wisdom of the economic solutions adopted for post-crisis recovery. Romania, a member state of the European Union, with relatively new democratic mechanisms and market economy, is an integral part of the global social, economic and political landscape.